Cognitive assessment of elderly people in outpatient care - Zortea, Bruna; Gautério-Abreu, Daiane Porto; Santos, Silvana Sidney Costa; Silva, Bárbara Tarouco da; Ilha, Silomar; Cruz, Vânia Dias (Rev Rene, 2015)
Objective: to evaluate the cognitive state of elderly people under outpatient care; investigate the association between the cognitive state and the socio-demographic variables, health conditions, number of medications and adhesion to the treatment. Methods: this is a cross-sectional, exploratory, and descriptive study, with a quantitative approach, conducted with 107 elderly people undergoing outpatient care in a university hospital in the south of Brazil. The following variables were used: gender, age, marital status, income, schooling, occupation, preexisting noncommunicable diseases, number and type of prescribed medications, adhesion, mini mental state examination and cognitive status. Data were analyzed through inferential and descriptive statistics. Results: The prevalence of cognitive deficit was of 42.1% and had a statistically significant connection with schooling, income, marital status, hypertension and cardiopathy. Conclusion: nurses can intervene to avoid the increase of cognitive deficit through an assessment of the elderly people, directed to facilitative strategies to soften this deficit.